Pengaruh Model Problem Based Learning (PBL) dengan Pendekatan Metakognitif Terhadap Self Regulated Learning (SRL) dan Hasil Belajar - Selvia Damayanti; Hafnati Rahmatan; Andi Ulfa Tenri Pada; Cut Nurmaliah; Samingan (Postgraduate, University of Mataram, 2026)
The implementation of Problem Based Learning (PBL) supported by a metacognitive approach has the potential to not only improve student learning outcomes but also develop Self-Regulated Learning (SRL) abilities. This study aims to examine the implementation of the Problem Based Learning (PBL) learning model with a metacognitive approach on student learning outcomes and self-regulated learning on Virus material. The study used a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of two classes, namely the experimental class given PBL treatment with a metacognitive approach, and the control class using the discovery learning model. Data analysis used an independent sample t-test and Pearson product moment with a significance level of 0.05. The results of the study on the effect of the application of PBL with a metacognitive approach on learning outcomes showed a sig. 0.00 <0.05. The results of the study on SRL showed that it was in the sufficient category. The results of the study on the relationship between SRL and learning outcomes showed a sig. 0.00 <0.05. Based on data analysis, it can be concluded that the application of the PBL model with a metacognitive approach has an effect on students' SRL abilities and learning outcomes. The SRL category of students in the experimental class was higher than that of the control class and was in the sufficient category. There is a significant relationship between SRL and student learning outcomes.